1998
DOI: 10.1074/jbc.273.39.25244
|View full text |Cite
|
Sign up to set email alerts
|

Human α1,3/4-Fucosyltransferases

Abstract: In a previous study (Xu, Z., Vo, L., and Macher, B. A. (1996) J. Biol. Chem. 271, 8818 -8823), a domain swapping approach demonstrated that a region of amino acids found in human ␣1,3/4-fucosyltransferase III (FucT III) conferred a significant increase in ␣1,4-FucT acceptor substrate specificity into ␣1,3-fucosyltransferase V (FucT V), which, under the same assay conditions, has extremely low ␣1,4-FucT acceptor substrate specificity. In the current study, site-directed mutagenesis was utilized to identify whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 34 publications
(33 reference statements)
1
19
0
Order By: Relevance
“…3 Interestingly, the disulfide linkage formed between Cys 59 and Cys 413 brings the amino acid residues located near the N and C termini of the catalytic domain within close proximity. This distinctive arrangement is similar to that occurring in ␣(1,3/1,4) fucosyltransferase III (51) and polysialyltransferase ST8Sia IV (52), where site-directed mutagenesis demonstrated that such steric conformation may be associated with acceptor substrate specificity (53,54) and catalytic efficiency (52), respectively. Similarly, the catalytic activity of GM2 synthase depends on the formation of disulfide-bonded homodimers, whose antiparallel orientation also brings the N and C termini in close proximity, most likely to establish a catalytic domain (55).…”
Section: Discussionmentioning
confidence: 78%
“…3 Interestingly, the disulfide linkage formed between Cys 59 and Cys 413 brings the amino acid residues located near the N and C termini of the catalytic domain within close proximity. This distinctive arrangement is similar to that occurring in ␣(1,3/1,4) fucosyltransferase III (51) and polysialyltransferase ST8Sia IV (52), where site-directed mutagenesis demonstrated that such steric conformation may be associated with acceptor substrate specificity (53,54) and catalytic efficiency (52), respectively. Similarly, the catalytic activity of GM2 synthase depends on the formation of disulfide-bonded homodimers, whose antiparallel orientation also brings the N and C termini in close proximity, most likely to establish a catalytic domain (55).…”
Section: Discussionmentioning
confidence: 78%
“…In particular, expression of the aromatic Trp 111 residue of FucT-III (corresponding to Trp 124 of FucT-V) has been shown to be primarily responsible for the type 1 chain acceptor specificity found in FucT-III and FucT-V (22). Additional evidence has demonstrated that higher type 1 chain specificity can be conferred upon FucT-V by substitution of Asn 86 and Thr 87 with His and Ile, respectively, amino acids found in the corresponding positions in FucT-III (20). Taken together, the results independently indicate that, in addition to having a role in defining type 1 versus type 2 chain specificity, amino acids in positions corresponding to Thr 87 and Trp 124 of FucT-V also function in defining a preference for the fucosylation of an internal versus distal GlcNAc residue of sialylated polylactosamines, leading to VIM2 or sialyl-Le x structures.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing amount of information is becoming available to show how specific amino acid residues within the more variable regions of the catalytic domain of these proteins influence specific properties of a given enzyme form (Refs. 17, 21, and 23-32; see also accompanying papers (34,36)). The results presented in this paper address a region of the catalytic domain that is instead rather highly conserved among enzyme forms.…”
Section: Discussionmentioning
confidence: 99%
“…Western Blot Analysis of pPROTA-expressed Enzymes-The pPROTAexpressed recombinant FucT enzymes were separated on 12% Tris/ glycine polyacrylamide gels, transferred to nitrocellulose membranes, and probed as described in an accompanying paper (34).…”
Section: Methodsmentioning
confidence: 99%